Compressed 3D Image Information and Communication Security. Issue 2 (22nd June 2018) - Yang, Chengshuai; Ding, Yuyang; Liang, Jinyang; Cao, Fengyan; Qi, Dalong; Jia, Tianqing; Sun, Zhenrong; Zhang, Shian; Chen, Wei; Yin, Zhenqiang; Wang, Shuang; Han, Zhengfu; et al.
Abstract: Ensuring information and communication security in military messages, government instructions, scientific experiments, as well as in personal data processing, is critical. In this study, a new hybrid classical–quantum cryptographic scheme to protect image information and communication security is developed by combining a quantum key distribution (QKD) and compressed sensing (CS). This method employs a QKD system to generate true random codes among the remote legitimate users and utilizes these random codes to encrypt and decrypt compressed 3D image information based on the CS algorithm. Therefore, this new technique can provide computational security in the image information transmission process by the encryption and decryption of CS algorithm, and the information and communication security can be evaluated in real time by monitoring the QKD system. Furthermore, this technique can directly transmit and reconstruct the compressed 3D image information based on the modified TwIST algorithm, and thus fewer random codes are required in QKD system, which can improve the information transmission bandwidth. Consequently, this technique not only provides a new application of a QKD system but also extends the CS‐based image reconstruction from 2D to 3D. This study may open a new opportunity in the field of information and security communication. Abstract : A new hybrid classical–quantum cryptographic technique by combining quantum key distribution with compressing sensing algorithm was proposed to safely transmit the compressed 3D image information. This approach can not only improve the information transmission bandwidth of both quantum and classical channels, but also can evaluate the image information and communication security in real time.